Animal, criticism and immunity in the poetry of Antonio Cisneros (Revista de Crítica Literaria Latinoamericana, 2016)
The poetry of the Peruvian poet Antonio Cisneros (1942-2012) is notable for its many animal figures. In this article, I intend to read these animal and insects figures through the lens of biopolitical theories and animal studies. My reading is based on two premises. In the first, Cisneros uses animals to make a social and political criticism, and also as a way to imagine another type of political community. In the second, Cisneros has his animals take a bodily presence to point out the blurring spatial boundaries between animals and humans. The notion of immunity produced by Esposito helps explain how these boundaries between species are maintained.
Keywords: peruvian poetry; latinamerican poetry; animales; biopolitics; literature